Determination genetic variation and phylogenetic analysis in Echinococcus granulosus isolated from Iraqi sheep - Bayraktar, M; Hussein, M; Hassan, H (Journal of the Hellenic Veterinary Medical Society, 2022)
Echinococcus granulosus causes Cystic Echinococcosis disease in intermediate hosts, such as sheep, cattle, goats, camels, and horses. Cystic Echinococcosis is an essential parasitic zoonosis that affects humans and animals and is a significant public health and economic problem worldwide. This study aimed to determine the molecular characterization and phylogenetic analysis of Echinococcus granulosus in sheep’s livers and lungs. The genetic variation was performed by directly sequencing the mitochondrial DNA (mtDNA) genes coding of the NADH dehydrogenase subunit 1 (ND1). The evidence from molecular studies and DNA sequencing revealed that the Isolates of Echinococcus granulosus in Kirkuk city related to the sheep strain G1 genotype. The alignment analysis showed a concordance between isolates with each other by 99%. When comparing the results with Genbank, it indicated the occurrence of genetic variations between nucleotides represented by eleven codons, seven of which represent transversion mutations, and four are transition mutations.